QARAQALPAQ QAHARMANLÍQ DÁSTANLARÍ TILINDE SINONIM FRAZEOLOGIZMLERDIŃ QOLLANÍLÍWÍ - Qutibaeva, A. (SCIENCE and SOCIETY, 2025)
In a scientific article, synonyms relate not only to lexicology, which is a large branch of lexicography, but are also associated with the formation and change of words in meaning. They say that as a result of the spiritual development of such synonyms, new sets of synonyms will appear.